Peroxymonosulfate-enhanced visible light photocatalytic degradation of bisphenol A by perylene imide-modified g-C3N4 - Zhang, Juanjuan; Zhao, Xu; Wang, Yanbin; Gong, Yan; Cao, Di; Qiao, Meng (Applied catalysis. B, Environmental, 2018)
[Display omitted] •PI-g-C3N4 exhibited higher photocatalytic activity than PTCDA and g-C3N4.•PMS largely increased degradation efficiency of BPA by PI-g-C3N4 photocatalyst.•O2−, 1O2, and h+ rather than SO4− were mainly responsible for BPA degradation.•The PI-g-C3N4 photocatalyst exhibited a high stability. In this study, a metal-free photocatalyst (PI-g-C3N4) was synthesized through an amidation reaction between perylene tetracarboxylic dianhydride (PTCDA) and graphitic carbon nitride (g-C3N4). In order to enhance the photocatalytic degradation efficiency of bisphenol A (BPA) by 5 wt% PI-g-C3N4, peroxymonosulfate (PMS) was introduced into this system. When 5 mM PMS was added, 96% of BPA with an initial concentration of 10 mg/L was degraded within 60 min; the pseudo-first-order degradation kinetics constant of BPA was increased from 0.0057 to 0.0501 min−1. Based on the photoelectrochemical analysis, it was proposed that PI-g-C3N4 achieved a more effective separation of photogenerated electron–hole pairs and displayed higher conductivity than PTCDA and g-C3N4 individually, thus promoting the PMS activation into active radicals by the photogenerated electrons. The BPA degradation was favored at high PMS concentrations under alkaline conditions. The slight inhibition effect of co-existing anions on the degradation of BPA followed the order: H2PO4− > NO3− ≈ HCO3−; Cl− had a remarkable positive effect on the degradation of BPA. The radical quenching tests and electron spin resonance results indicated that O2−, 1O2, and h+ were the major species for the degradation of BPA. Combined with intermediates analysis, the degradation mechanism and pathway of BPA was proposed. The high stability of the 5 wt% PI-g-C3N4 was finally demonstrated.